Assessment of nutritional, antinutritional, antioxidant and functional properties of different soybean varieties: implications for soy milk development - Kehulum Getaneh Zewudie; Habtamu Fekadu Gemede (Cogent Food & Agriculture)
This study investigated the nutritional, antinutritional, functional, and antioxidant properties of six different soybean seed varieties collected from the Bako Agricultural Research Center (BARC), Ethiopia. The proximate composition of the soybean seed varieties varied significantly from one variety to another. The moisture content ranged from 8.44 to 9.66 g/100 g dry weight basis, crude protein ranged from 35.31 to 47.63 g/100 g, crude fat ranged from 17.53 to 23.75 g/100 g, crude fiber ranged from 5.85 to 11.43 g/100 g, crude ash ranged between 3.4 to 4.8 g/100 g, utilizable carbohydrate ranged from 4.16 to 27.19 g/100 g, and gross energy ranged from 409.82 Kcal/100g to 429.98 Kcal/100g. The minerals in mg/100 g of seeds of soybean varieties also had the following ranges: sodium 2.94 to 4.06, potassium 1062.04 to 1360.80, calcium 174.16 to 268.84, magnesium 153.30 to 204.54, iron 9.84 to 14.30, copper 1.16 to 1.93, zinc 3.24 to 4.61, and phosphorus 691.73 to 1124. In particular, Gute-19 soybean varieties contained significantly high amounts of crude protein, ash, crude fat, calcium, iron, and zinc. Principal component analysis showed nutritional variability and six independent clusters in varieties; this category was useful for preparing products such as soymilk. The antinutrient in mg/100 g of soybean varieties ranges as follows: phytate 198.53 (Keta) to 271.84 (Gute-19), oxalate 1580 to 2020, and tannin 134.93 to 191.62. The molar ratios of the soybean varieties in this study were below the critical/standard value, except for the phytate: Fe ratio. The soybean varieties had total phenol ranges from 1.19 to 2.02 mg GAE/g and total flavonoids from 0.25 to 0.81 mg CE/g. The IC50 values (mg/mL) of the soybean varieties were as follows: DPPH scavenging is 2.10-10.30. The antioxidant activity of all soybean varieties was high, with Gute-19 exhibiting the highest antioxidant activity. Hence, increasing the cultivation, promotion, and consumption of soybean in the country could help in new product development, in addition to soymilk and food supplementation, and mitigate food insecurity and alleviate malnutrition in the country.